Prevalence and Characteristics of Low Back Pain among Productive Age Population in Jatinangor - Dini Diwayani Novitasari; Henny Anggraini Sadeli; Arifin Soenggono; Yulia Sofiatin; Hadyana Sukandar; Rully M. A. Roesli (Althea Medical Journal, 2016)
Background: Low back pain is one of the global health issues which prevalence is high among productive ages. It oftentimes corresponds with one’s physical activity during work . The purpose of this study was to determine theprevalence and characteristics of low back pain among productive age population in Jatinangor, West Java, Indonesia.Methods: This study was a cross-sectional descriptive study conducted during the period of August to October 2014 in the three villages in Jatinangor, West Java, Indonesia. In order to determine the demographic data and history of low back pain in the last three months, about 1075 productive age populations were selected through validated questionnaire as the secondary data. These data consisting of 310 subjects were then described according to the pain characteristics and physical activity during work.Results: During three months of examination, s the prevalence of low back pain was 38.4%, with the average age 50–59 years old. Furthermore, about 22.3% subjects were indicated chronic low back pain. The most prevalent qseverity of the pain was dull pain (29.4%), followed with pins and needles pain (23.1%), As the intensity of the pain increased, there was a tendency of increasing interference in daily activities. Static posture was also the most frequent physical activity during work (53.2%).Conclusions: The prevalence of low back pain is more than one third (38.4%) among productive age populations in Jatinangor, West Java, Indonesia.[AMJ.2016;3(3):468–75]DOI: 10.15850/amj.v3n3.863